TRANSFORMATION OF THE FIRST CONSOLIDATED STATEMENTS, IFRS - Anna V. Chernyavskaya (Вестник Северо-Кавказского федерального университета)
Questions preparation of the first IFRS financial statements are now more urgent. Many Russian companies decide to start preparation of the consolidated financial statements under IFRS in order to attract foreign investment. Article detail reveals the basis for the formation of the first IFRS financial statements , which is an urgent issue for many Russian companies , as well as for a wide range of experts in the preparation of financial statements under IFRS